Role of computational efficiency indices and pose clustering in effective decision making: An example of annulated furanones in Pf-DHFR space. (April 2017) - Kumar, Manoj; Kaur, Tanpreet; Sharma, Anuj
Graphical abstract: Highlights: Efficiency indices and pose clustering was used for effective decision making. Method was validated by experimental SARs. As an example 720 furanones were docked against Pf -DHFR binding site. Scaffold class I (Indandione derived) performed better in efficiency plane. Introduction of polarity in isocyanide decreased the drug likeness of furanones. Abstract: In the present report, the role of computationally estimated efficiency indices and pose clustering has been demonstrated in effective decision making, resource management and chemical prioritization. As an example, 720 annulated furanones from six different scaffold classes were computationally docked against Pf -DHFR active site using AutoDock 4.2. Many trends were established by navigating efficiency indices (BEI and SEI) in 2D planes. These trends were then explained by comparing interaction profiles of docked poses with that of known actives/inhibitors. Cases where trends emerged from efficiency plots resonated well with the pattern of a particular cluster diagram were considered as guidelines for optimization purpose. These kind of guidelines can help medicinal chemists in prioritization their work and in effective management of time, energy and chemical resources.